“How Could One Understand You?” (About the Difficulties in Human Communication) - Stoškus, Krescencijus (Problemos, 1969)
According to existentialistic tradition standardization and formalism is one of the main barriers in intersubjective communication. The paper attempts to prove that there is no purely standard communication. Standardization of expressions and general meanings usually gives rise to new latent meanings, which serve to express individual’s private intentions, predispositions, emotions, etc. Under definite conditions these intentions and predispositions are easily foreseen by the addressee. On the other hand highly original ideas, indefinite intentions of an individual may often present difficulties of understanding for the addressee. Communication difficulties may arise because of discrepancy in the individual experience of communicators, differences in symbolic systems used, contradictions in a world outlook, incompatibility of temperament, etc. Therefore it is possible to discover in what is called mutual understanding a moment of incomprehension, though it is not necessarily experienced by the communicators as in communicability. The author holds that these conclusions may prove to be of major methodological significance in solving the problems associated with incommunicability of modern man.